Fasting blood glucose--a missing variable for GFR-estimation in type 1 diabetes? - Petter Bjornstad (Public Library of Science (PLoS), 2014)
Objective Estimation of glomerular filtration rate (eGFR) is one of the current clinical methods for identifying risk for diabetic nephropathy in subjects with type 1 diabetes (T1D). Hyperglycemia is known to influence GFR in T1D and variability in blood glucose at the time of eGFR measurement could introduce bias in eGFR. We hypothesized that simultaneously measured blood glucose would influence eGFR in adults with T1D. Methods Longitudinal multivariable mixed-models were employed to investigate the relationships between blood glucose and eGFR by CKD-EPI eGFRCYSTATIN C over 6-years in the Coronary Artery Calcification in Type 1 diabetes (CACTI) study. All subjects with T1D and complete data including blood glucose and cystatin C for at least one of the three visits (n = 616, 554, and 521, respectively) were included in the longitudinal analyses. Results In mixed-models adjusting for sex, HbA1c, ACEi/ARB, protein and sodium intake positive associations were observed between simultaneous blood glucose and eGFRCYSTATIN C (β±SE:0.14±0.04 per 10 mg/dL of blood glucose, p<0.0001), and hyperfiltration as a dichotomous outcome (OR: 1.04, 95% CI: 1.01-1.07 per 10 mg/dL of blood glucose, p = 0.02). Conclusions In our longitudinal data in subjects with T1D, simultaneous blood glucose has an independent positive effect on eGFRCYSTATIN C. The associations between blood glucose and eGFRCYSTATIN C may bias the accurate detection of early diabetic nephropathy, especially in people with longitudinal variability in blood glucose.